PENGARUH EKUITAS MEREK PRODUK SUSU BEAR BRAND TERHADAP PERILAKU PEMBELIAN KEMBALI PASCA PANDEMI COVID 19 - Dwitama, Ikhtiar Kurnia; Handaruwati, Indah (Universitas Sahid, 2024)
The Covid-19 pandemic has caused panic buying of certain products such as hand sanitizers, masks, vitamins and bear brand dairy products. This change in behavior resulted in the product being scarce and experiencing an increase in price. This study aims to provide empirical evidence of the brand equity dimension, namely awareness, association, perception of quality and brand loyalty partially and simultaneously on Buyback Behavior. The research method used is quantitative. The population in this study is consumers of bear brand milk, with a sample of 105 people. The determination of the sample was carried out by the purposive sampling method with the characteristics of consumers who had consumed dairy products during the pandemic and were still consuming until after the pandemic. Data processing using SPSS. The results of this study are known to have an influence between brand equity and repurchase decisions. Consumer loyalty in making repeat purchases is due to consumer awareness of health by consuming milk.